Ethical Leadership and Administrative Competence: A Study of Ethiope East and Ethiope West Local Government Areas of Delta State, Nigeria - Gbosien Chris, SOKOH (International Journal of Psychosocial Rehabilitation, 2024)
Unethical and administrative corrupt practices have emerged as part of the criticismsleveled against local governments in Nigeria. Perhaps, the problem of employees’ apathy andlack of effort to perform the core functions of a modern state is not simply a matter of laziness;rather, there are often healthy reactions by normal people to an unhealthy environment createdby unethical leadership. This underscores the importance of ethical leadership in influencingadministrative competence. It is against this backdrop that this study examines the relationshipbetween ethical leadership and administrative competence in Ethiope Easst and Ethiope WestLocal Government Areas of Delta State, Nigeria. A cross-sectional survey research design wasadopted and data was collected via a survey of 177 respondents randomly selected from apopulation of 317 employees of the Ethiope East and Ethiope West Local Governments. Datacollected were analyzed using correlation and linear regression analysis with the aid ofStatistical Package for Social Science (SPSS) version 23. The results of the study revealed thatthere is a significant relationship between ethical leadership and administrative competence ofemployees. The study also showed that ethical leadership exerts a positive and statisticallysignificant effect on administrative competence in Ethiope East and Ethiope West LocalGovernment Areas of Delta State, Nigeria. Based on these findings, the study concludes thatethical leadership has significant influence on administrative competence. The study thereforerecommendes among others that local government leadership should rewards ethical conductand discipline unethical conduct by exhibiting ethical behaviour that promote administrativecompetent.